Variations in Elephant (Loxodanta africana) Diet Along a Rainfall Gradient: The Effect of Latitude, Grass Reserves, and Proximity to Water - Booth, Laura; Breen, Catherine; Gullickson, Cricket (Consilience, 2015)
Global climate change is predicted to bring longer dry seasons and changing rainfall patterns to equatorial Africa, causing range reductions for species such as elephants, whose diets are constrained by water availability. Elephants are facultative grazers whose diets are seasonal, with woody proportion of diet increasing in the dry season. In this study, we sought to identify the factors that predict woody percentage of elephant diet along a rainfall gradient at the Mpala Research Centre in central Kenya. We used elephant dung as a means to analyze the woody content of elephant diet. We found that grass biomass and distance to the nearest river explained the most variability in elephant diet, while latitude was a less influential predictor. Because these local factors were more important determinants of elephant diet differences than rainfall along a gradient, we conclude that climate change will likely affect elephant populations through elongated dry seasons, which may limit availability of nearby water sources.